Tinjauan Hukum Ekonomi Syariah terhadap Pengelolaan Zakat Produktif di BAZNAS Kabupaten Bogor - Moh. Asep Zakariya Ansori; Aura Khalifa; Moh. Zainal Muttaqin; Milka Nurul Hikmah; Yani Oktaviani; Elika Nur Padilah; Muhammad Pikri Saepulloh (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to analyze the management of productive zakat in Indonesia, specifically by the National Zakat Agency (BAZNAS), from the perspective of Islamic economic law. The method used is literature study by examining secondary data in the form of laws, regulations, books, journals, and reports related to the topic of discussion. The results of the analysis show that the management of productive zakat by BAZNAS is generally in accordance with the provisions of Islamic economic law. However, there are still some weaknesses in the empowerment mechanism that need to be addressed so that the goal of empowering the economy of the Muslim community can be achieved maximally.